A numerical model for risk of ball-impact injury to baseball pitchers - Nicholls, R. L.; Miller, K.; Elliott, B. C. (Medicine & Science in Sports & Exercise, 2005)
Introduction: Metal baseball bats produce higher ball exit velocity (BEV) than wood bats, increasing the risk of impact injuries to infield players. In this paper, maximum BEV from a wood and a metal bat were determined using the finite element method. Methods: Three-dimensional (3-D) bat kinematics at the instant of impact were determined from high-speed videography (N = 17 high-performance batters). A linear viscoelastic constitutive model was developed for stiffer and softer types of baseballs. The risk of impact injury was determined using available movement time data for adult pitchers; the data indicate that 0.400 s is required to evade a batted ball. Results: The highest BEV (61.5 m[middle dot]s-1) was obtained from the metal bat and the stiffer ball model, equating to 0.282 s of available movement time. For five impacts along the long axis of each bat, the "best case scenario" resulted from the wood bat and the softer ball (46.0 m[middle dot]s-1, 0.377 s). Conclusions: The performance difference between the bats was attributed to the preimpact linear velocity of the bat impact point and to differences in orientation on the horizontal plane. Reducing the swing moment of the baseball bat, and the shear and relaxation modulii of the baseball, increased the available movement time.